Os marcadores metadiscursivos em textos didáticos especializados: um estudo em corpora em língua alemã - Carvalho, Ednúsia Pinto de (2005)
This dissertation describes and explains the functions and the frequency of the textual metadiscourse markers: (1) “reformulative markers of explanation” (2) “reformulative markers of correction (or repair)”, (3) “reformulative markers of exemplification”, and (4) interpersonal markers (relational and personal). Our assumption is that the presence of these markers in didactic texts could reduce the information density which would facilitate the reading process. In order to perform this investigation, the following materials on reading comprehension were used: the book “Didaktik des Lesevertehens” and the distance learning module “Fertigkeit Lesen” both written in German by Westhoff. This research is based on the studies of Hoffmann (1998), Textual Terminology, and Hyland (1998), Metadiscourse. To gather and analyze the data, we utilized Corpus Linguistics methodology, especially a computational tool called WordSmith (Scott, 1997). The research results suggest that a more pronounced use of metadiscourse markers may improve reading comprehension and increase interaction between readers and writers. Finally, this study aims to help the German for Specific Purposes (GSP) teachers to understand the specialized texts as a product and a tool of a specific specialized communication within a communicative context.